Class Distinction and Its Social Implication in Capitalist Society as Depicted in George Bernard Shaw’s Pygmalion - Yohanes Tuaderu (STBA Prayoga Padang, 2015)
Class distinction is a differentiation of social class in capitalist society in which the dominant class i.e., the capital owners exploit the subordinate class i.e., the working class to gain big economic profit in the process of mass production. The extreme class distinction results in form of bad treatments such as low wages, long working hours (12 to 19 hours per day), and the imposition of bad discipline and fine system. The objective of this research was to reveal the class distinction encountered by the main character – Liza Doolittle – in George Bernard Shaw’s Pygmalion as a reflection of a real social condition in capitalist society. In fact, this condition has brought along with it some social implications toward the society such as dehumanization, human exploitation, and poverty that affectsocial life of British people all over the country. This was a qualitative research using two main theories i.e., 1) Theory of Homology postulated by Lucien oldmann which was used to prove the interdependent relationship between the society which is told in Shaw’s Pygmalion and the real society in England, and 2) Marxist criticism of some scholars which is utilized to analyze class distinction in Pygmalion which is assumed as the portrait of the unstopped struggle of the proletariat to achieve their rights ignored by the bourgeoisie for hundreds of years. The result of the study showed that the social condition in England in the end of nineteenth century to the early twentieth century was mostly affected by the practice of class distinction and human exploitation in industry sphere. Meanwhile, the class struggle which was experienced by the main character of Pygmalion was the portrait of the struggle of the working class to free themselves from poverty, to release them from the capitalist’ oppression, and to gain the admission from the society that they have equal dignity as other human beings in society.